Appropriation through guided participation: Media literacy in children׳s everyday lives. (June 2016) - Aarsand, Pål; Melander, Helen
Abstract: This article explores media literacy practices in children׳s everyday lives and some of the ways in which young children appropriate basic media literacy skills through guided participation in situated activities. Building on an ethnomethodological perspective, the analyses are based on video recordings documenting the activities in which four target children, aged 6–7 years old, participated at home and in school. Through the detailed analysis of two mundane media literacy activities – online calling and word processing – similarities and differences in media usage within and out-of-school are examined. It is shown how children׳s media literacy activities encompass verbal, embodied and social competencies that are made relevant, and thus accessible for learning, in interaction between the adults and children in the form of norms and guidelines for what constitutes knowledgeable participation in media literacy activities, and that are appropriated and reactualized by the children in interaction with their peers. The findings show how the participants coordinate their actions on and in front of the screen and where spatiality and temporality are oriented to as crucial aspects of the organization of the activities. Moreover, it is demonstrated how old and new technologies are linked together in culturally and historically embedded conceptualizations of literacy. Highlights: Norms are appropriated and reactualized by children in media literacy activities. Temporality is a crucial aspect of the organization of media literacy activities. Spatiality is a crucial aspect of the organization of media literacy activities. Old and new technologies are linked in socially embedded conceptualizations of literacy. Basic skills in handling the media technology are taken for granted in school.